Polymer-coated polyethylenimine/DNA complexes designed for triggered activation by intracellular reduction. - Carlisle, R; Etrych, T; Briggs, S; Preece, J; Ulbrich, K; Seymour, L (2004)
BACKGROUND: Site-specific gene delivery requires vectors that combine stability in the delivery phase with substantial biological activity within target cells. The use of biological trigger mechanisms provides one promising means to achieve this, and here we report a transfection trigger mechanism based on intracellular reduction. METHODS: Plasmid DNA was condensed with thiolated polyethylenimine (PEI-SH) and the resulting nanoparticles surface-coated using thiol-reactive poly[N-(2-hydroxypropyl)methacrylamide] (PHPMA) with 2-pyridyldisulfanyl or maleimide groups, forming reducible disulphide-linked or stable thioether-linked coatings, respectively. RESULTS: Both sets of polymer-coated complexes had similar size and were stable to a 250-fold excess of the polyanion poly(aspartic acid) (PAA). Reduction with dithiothreitol (DTT) allowed complete release of DNA from disulphide-linked coated complexes, whereas complexes with thioether-linked coating remained stable. Disulphide-linked complexes showed 40-100-fold higher transfection activity than thioether-linked ones, and activity was selectively further enhanced by boosting intracellular glutathione using glutathione monoethyl ester or decreased using buthionine sulfoximine. The chloroquine- and serum-independent transfection activity of disulphide-linked coated complexes suggests this system may provide a viable trigger mechanism to enable site-specific transfection in complex biological settings. CONCLUSIONS: Linkage of hydrophilic polymer coating to PEI/DNA complexes via reducible disulphide bonds offers a means of fulfilling the contradictory requirements for extracellular stability and intracellular activity.